(untitled) (Architecture Image Studies, 2024)
The Covid-19 virus has significantly affected the development of the world economy; moreover, this influence has turned out to be quite ambiguous. In this paper, the emphasis was placed on considering the development trends of construction companies and the primary housing market. Thus, the main objectives of the work are to assess the impact of the COVID-19 crisis on this sector of the economy and to assess possible trends in its development in the future. The main method in writing the work was the method of analysis conditioned upon the large number of processed statistical data on the development of the construction sector and the housing market in the countries of the world. During the analysis, the author came to the conclusion that the development trends of construction companies in the countries of the world as a whole have a similar trend: all of them have suffered significantly from the pandemic and its limitations. However, there are some negative trends depending on the regions and countries; it was shown that the state of construction companies largely depended on how the state reacted to the newly appeared problems, how active and fast it was. Prices on the housing market showed a significant increase, which is also primarily explained by the policy of states to support businesses (mainly small) and local residents in connection with the pandemic, which means an increase in their ability to pay.